Zur Agrarlandschaftsentwicklung in Transguadianaland (Portugal) - Freund, Bodo (ERDKUNDE, 1972)
After 1834, the estates of the religious orders in the part of Alentejo Province which lay east of the Guadiana were auctioned following liberal legislation, so that a situation of large private landholdings was created. Apart from this, distribution of the extensive common lands (Allmenden) to all local families occurred almost everywhere, and this led to a broad scatter of small-scale ownership. In addition large landowners fragmented large areas of their more extensively-farmed estates in order to increase their profits and released the plots under various conditions (outright sale, leasehold, short leases) to landless peasants and small farmers. These people were forced into labour-intensive use of their small holdings (grain, permanent crops). The economic and governmental dominance of the estate landlords prevented the development of co-operative security for the small farmers so that they were especially hard hit by crises. Since they could not permanently protect their holdings from indebtedness they mostly lost their independence. Because of this, large estates today dominate by far, in terms of area - the intensification of land use by the small farmer has thus been to their benefit. Because of the mechanisation of field cultivation, many agricultural workers and small peasants have emigrated since 1955. Shrinkage in the labour force can be partly countered by changes in production methods (innovations). The shortage of labour will, however, cause problems in the future in the use of plots which cannot be mechanised and in the cultivation of permanent crops (holm oaks, olives, vines).